The Relevance Between An ESP Syllabus And The Students’ Needs - Miftakh, Fauzi (Journal of English Education Studies, 2018)
In learning English for specific purpose, students sometimes do not get appropriate materials with their needs. ESP materials are more specific than general English, so students should receive materials related to their background of field. This research aimed at finding out the relevance between an ESP syllabus and the students’ needs. This research used qualitative method that deals with a single or small-case studied in detail. The population was taken from the 1st semester students of Mechanical Engineering Department at University of Singaperbangsa Karawang. Random sampling was 24 students that was taken from two classes out of 120 students. The data was taken by distributing questionnaire to students and analyzing the syllabus designed by teacher. The result of this research shows that most students who are working in companies need to learn speaking skill as the most important skill as well as grammar. In addition, the ESP syllabus provided by teacher is quite relevant to the students’ needs. Therefore, it is suggested that teacher conducts a need analysis to students before designing syllabus, so it can be relevant with the students’ needs.